A combined process integration and fuel switching strategy for emissions reduction in chemical process plants - Mahmoud , A.; Mahadzir, Shuhaimi; Abdel Samed, M (Elsevier, 2009)
The combustion of fossil fuel to provide process heating is the major source of atmospheric pollution. Combustion products such as carbon dioxide, oxides of sulfur, oxides of nitrogen and particulates are known to be the major causes for global warming, acid rains and smog. This paper presents a combined method of fuel switching and heat exchanger network(HEN)retrofit to reduce flue gas emissions. The method is demonstrated using pre-heat train of a crude oil distillation unit as the case study.Target emissions reduction of 50%is achieved at an approximate payback period of 0.44 year on the capital investment due to the combination of the two methods.